Pink princess rules the school - Crowne, Alyssa, 1965-; Alder, Charlotte (New York : Scholastic, 2009)
Juliet Henry is planning a party for her seventh birthday, and she wants to invite only girls and have everything pink, from the food to the outfits. But the boys in her class don't want to be left out of the fun. Will they spoil the pink princess party?
"Little Apple."
Reading level: 1.9.
Guided reading level: O.
JCPF (ordered JF) ak
Keywords: Birthday parties -- Juvenile fiction; Pink -- Juvenile fiction; Girls -- Juvenile fiction; Schoolboys -- Juvenile fiction; First chapter book